2017
DOI: 10.1111/sltb.12401
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Harassment–Suicide Connection in the U.S. Military: Contextual Effects of Hostile Work Environment and Trusted Unit Leaders

Abstract: Sexual harassment has been associated with suicidal behaviors, and with the rise in suicides in the U.S. military, sexual harassment's role in suicide has been of growing interest. Lacking are studies that examine group- or unit-level variables in the relationship of sexual harassment to suicidal behaviors (thoughts, plans, and attempts). In this study, survey data from soldiers (12,567 soldiers in 180 company-sized units) who completed the Unit Risk Inventory administered during calendar year 2010 were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…Fourteen studies (29.8%) assessed the relation between MST and suicidal behaviors. MST was found to be significantly associated with suicide ideation (Bryan et al, 2015; DiMauro et al, 2018; Gradus et al, 2013a; Griffith, 2017; Klingensmith et al, 2014; Monteith et al, 2015, 2016a, 2016b; Schry et al, 2015; Stahlman et al, 2015), suicide plan (Bryan et al, 2015; Griffith, 2017), and suicide attempt (Bryan et al, 2015; Gradus et al, 2013b; Griffith, 2017; Klingensmith et al, 2014; Monteith et al, 2016a; Rosellini et al, 2017; Stahlman et al, 2015), with one exception: Beckman et al (2018) found that MST was not significantly associated with past year suicide ideation. Further, one study found that a history of MST was associated with increased odds of suicide mortality (Kimerling et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (29.8%) assessed the relation between MST and suicidal behaviors. MST was found to be significantly associated with suicide ideation (Bryan et al, 2015; DiMauro et al, 2018; Gradus et al, 2013a; Griffith, 2017; Klingensmith et al, 2014; Monteith et al, 2015, 2016a, 2016b; Schry et al, 2015; Stahlman et al, 2015), suicide plan (Bryan et al, 2015; Griffith, 2017), and suicide attempt (Bryan et al, 2015; Gradus et al, 2013b; Griffith, 2017; Klingensmith et al, 2014; Monteith et al, 2016a; Rosellini et al, 2017; Stahlman et al, 2015), with one exception: Beckman et al (2018) found that MST was not significantly associated with past year suicide ideation. Further, one study found that a history of MST was associated with increased odds of suicide mortality (Kimerling et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We are aware of only a few previous studies on this topic. For example, Griffith (2019) showed an association between workplace sexual harassment and suicide attempts in the US,27 and Jin et al (2018) showed an association with self-harm in Taiwan 28. However, both of these studies included military personnel only, used a cross sectional design, and studied only suicide attempts and not suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of sexual harassment among military women are well-established (Department of Defense, 2019; Morral & Gore, 2017), as are the associations between sexual harassment and negative outcomes, which include poorer physical health (Street et al, 2008), depression (Street et al, 2008), anxiety (Murdoch & Nicol, 1995), post-traumatic stress disorder (PTSD; Street et al, 2013), problematic alcohol use (Gradus, et al, 2013), and suicidality (Griffith, 2019; Khan et al, 2019). Less is known about variables that may explain these associations.…”
Section: Introductionmentioning
confidence: 99%